Skeletal adverse events in childhood cancer survivors : An Adult Life after Childhood Cancer in Scandinavia cohort study - ALiCCS study group; Oskarsson, Trausti; Duun-Henriksen, Anne Katrine; Bautz, Andrea; Madanat-Harjuoja, Laura; Falck Winther, Jeanette (International Journal of Cancer, 2021)
The dynamic growth of the skeleton during childhood and adolescence renders it vulnerable to adverse effects of cancer treatment. The lifetime risk and patterns of skeletal morbidity have not been described in a population-based cohort of childhood cancer survivors. A cohort of 26 334 1-year cancer survivors diagnosed before 20 years of age was identified from the national cancer registries of Denmark, Finland, Iceland and Sweden as well as a cohort of 127 531 age- and sex-matched comparison subjects randomly selected from the national population registries in each country. The two cohorts were linked with data from the national hospital registries and the observed numbers of first-time hospital admissions for adverse skeletal outcomes among childhood cancer survivors were compared to the expected numbers derived from the comparison cohort. In total, 1987 childhood cancer survivors had at least one hospital admission with a skeletal adverse event as discharge diagnosis, yielding a rate ratio (RR) of 1.35 (95% confidence interval, 1.29-1.42). Among the survivors, we observed an increased risk for osteonecrosis with a RR of 25.9 (15.0-44.5), osteoporosis, RR 4.53 (3.28-6.27), fractures, RR 1.27 (1.20-1.34), osteochondropathies, RR 1.57 (1.28-1.92) and osteoarthrosis, RR 1.48 (1.28-1.72). The hospitalization risk for any skeletal adverse event was higher among survivors up to the age of 60 years, but the lifetime pattern was different for each type of skeletal adverse event. Understanding the different lifetime patterns and identification of high-risk groups is crucial for developing strategies to optimize skeletal health in childhood cancer survivors. Peer reviewed